2001
DOI: 10.1144/gsl.sp.2001.184.01.14
|View full text |Cite
|
Sign up to set email alerts
|

The response of mineral chronometers to metamorphism and deformation in orogenic belts

Abstract: Mineral chronometers, especially accessory minerals using the U-Pb decay system, can reveal important information regarding the environmental conditions and duration of metamorphic-deformation events during the re-working of older rocks. Minerals such as zircon can newly grow during amphibolite facies or granulite facies events, providing direct ages of metamorphism. Pre-existing minerals like monazite, allanite, and titanite can preserve a component of their original age in spite of upper amphibolite facies r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…The robustness of allanite is even more significant in samples from Bellinzona and Val d'Arbedo where there is good evidence of prolonged high temperatures from zircon dating and Ti-in-zircon thermometry ). This observation is consistent with, and improves on other empirical estimates of Pb closure temperature in allanite from high-grade gneisses ($650°C, Heaman and Parrish, 1991;Parrish, 2001) and calc-alkaline igneous rocks (700-800°C, von Blanckenburg et al, 1992;Oberli et al, 2004).…”
Section: Isotopic Resetting In Allanitesupporting
confidence: 90%
See 1 more Smart Citation
“…The robustness of allanite is even more significant in samples from Bellinzona and Val d'Arbedo where there is good evidence of prolonged high temperatures from zircon dating and Ti-in-zircon thermometry ). This observation is consistent with, and improves on other empirical estimates of Pb closure temperature in allanite from high-grade gneisses ($650°C, Heaman and Parrish, 1991;Parrish, 2001) and calc-alkaline igneous rocks (700-800°C, von Blanckenburg et al, 1992;Oberli et al, 2004).…”
Section: Isotopic Resetting In Allanitesupporting
confidence: 90%
“…Heaman and Parrish (1991) dated allanite from high grade gneisses by ID-TIMS and found that when metamorphosed to second sillimanite zone, protolith allanite still preserved a component of its original age. Parrish (2001) concluded based on U-Pb isotope systematics that the closure temperature of allanite is likely $650°C. Isotopic inheritance in the form of inherited cores has not been reported for allanite.…”
Section: Introductionmentioning
confidence: 99%
“…Age data include 40 Ar/ 39 Ar dates obtained for amphibole, biotite, and muscovite separates this study), U-Pb zircon dates Lee et al, 2003;Song et al, 2007;Liang et al, 2008), and fission track dates for zircon and apatite (Chung, 2006). Closure temperatures are taken from Parrish (2001).…”
Section: Implications For Miocene Tectonicsmentioning
confidence: 99%
“…U-Pb age data on zircon, allanite and titanite extracted from rocks associated with the metamorphic core zone of southeast British Columbia have shown the retentivity of radiogenic Pb in allanite to exceed that of titanite at upper amphibolite facies conditions (Heaman and Parrish, 1991). A closure temperature of 650 Ϯ 25°C was derived from these observations (Heaman and Parrish, 1991;Spear and Parrish, 1996;Parrish, 2001). As will be demonstrated by the isotopic arguments following below, such a low closure temperature appears to be at variance with our results.…”
Section: Isotopic Closure Of Zircon and Allanitementioning
confidence: 99%